Peaches - Anderson, Jodi Lynn (HarperTeen, 2012)
Three teenaged girls from very different backgrounds, thrown together to pick peaches in a Georgia orchard, spend a summer in pursuit of the right boy, the truest of friends, and the perfect peach.